International Accounting and Reporting Issues - 2008 Review - United Nations Conference on Trade; Development (United Nations, 2011)
Since the middle of 2007, world financial markets have been experiencing extreme turbulence. The centrality of reliable and comparable information for financial stability and for the ability of investors to assess risk and allocate resources to different investment opportunities has been painfully demonstrated by recent events. In marking UNCTAD’s Intergovernmental Working Group of Experts on International Standards of Accounting and Reporting (ISAR)’s twenty-fifth anniversary, the UNCTAD secretariat organized a high-level segment that featured prominent speakers, including ministers, discussing the positive contribution of international accounting and reporting standards and codes to financial stability and economic growth. This publication contains ISAR’s deliberations at its twenty-fifth session, and it will provide policymakers, regulators, standard-setters, boards of directors, researchers and other readers with insights into some of the timely issues on corporate reporting.